Agricultural Rural Marketing in India - Dutta, P. K. (Indian Journal of Marketing, 2011)
Marketing is an art of creating demand in the minds of the People. Once the demand is created, people will automatically go for the product. Marketing is the management process responsible for identifying, anticipating and satisfying customer requirements in a profitable way. The overall object of marketing is to ensure that the company obtains the revenue it needs to achieve its profit targets, and this is equally applicable to Rural Marketing in India. India’s rural markets are on a high tide, as many corporates involved in consumer goods, FMCGs, and financial services companies are making forays into rural areas: At the same time, small enterprises from the rural areas, which primarily fall under the unorganized sector, are emerging fast and making inroads into the hitherto unexplored domain of urban markets. We have now successful examples of SEWA, Lijat papad, AMUL, products of handicraft, cottage industries etc, making a beeline for the one billion strong Indian rural and urban markets. This paper discusses the present scenario of rural marketing, especially rural produce, and its importance, current trends, and highlights certain problems related to rural marketing. Further, it highlights the improvements that make the rural marketing system most effective. Additionally, the rural economy has not been impacted by the global economic slowdown. Significantly, the rural markets are also offering great opportunities to marketers, who are trying to find a way out of the current economic crisis. Rural and small town economy, which accounts for 60% of India’s income, has remained insulated from the economic slowdown as employment opportunity and income streams are intact and growing steadily with consistent demand for goods and services. The importance of the rural sector and the latest programs, policies and initiatives taken by the government and corporates in this regard are also discussed in the paper. Rural areas exhibit several distinctive characteristics that are different from the urban areas. Literacy levels, family structure, occupational patterns, spatial distribution of household settlements, social customs and norms, and several other features, are unique to rural India.